2014
DOI: 10.3748/wjg.v20.i18.5396
|View full text |Cite
|
Sign up to set email alerts
|

Non-platinum-based chemotherapy for treatment of advanced gastric cancer: 5-fluorouracil, taxanes, and irinotecan

Abstract: Despite numerous advances in treatment options, advanced gastric cancer (AGC) remains a major public health issue and the leading cause of cancer-related deaths. Cisplatin is one of the most effective broad-spectrum anticancer drugs for AGC and a doublet combination regimen of either cisplatin-based or 5-fluorouracil (5FU)-based chemotherapy is generally used for treatment of patients with AGC. However, there is still no consensus on the best regimen for treating AGC. Recently, various new chemotherapeutic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Fluorouracil (Fu)-based chemotherapy has been widely used as chemotherapy for gastric cancer (12). Large clinical studies of REAL-2 and ML17032 demonstrated the value of oral Fu drugs, including capecitabine, as a first-line treatment…”
Section: Introductionmentioning
confidence: 99%
“…Fluorouracil (Fu)-based chemotherapy has been widely used as chemotherapy for gastric cancer (12). Large clinical studies of REAL-2 and ML17032 demonstrated the value of oral Fu drugs, including capecitabine, as a first-line treatment…”
Section: Introductionmentioning
confidence: 99%
“…The current standard practice for treating advanced gastric cancer (AGC) is a doublet combination regimen of either platinum-based or 5-fluorouracil (5FU)based chemotherapy (1). Also, various new chemotherapeutic agents, including oral 5FU, irinotecan, and taxanes, have been identified to improve the outcomes for AGC (2). A recent targeted-agent trial showed that the addition of trastuzumab to conventional chemotherapy significantly improved the survival of patients with human epidermal receptor 2 (HER2)-positive AGC (3).…”
mentioning
confidence: 99%
“…Cisplatin was one of the first chemotherapeutic agents employed for many human cancers and keeping its popularity as the most widely used anticancer agent. Doublet therapy with platinum drugs, generally cisplatin in combination with either infused 5FU or an oral 5FU, is current standard application in many countries [12,13]. The aim of the current study was to investigate the cytotoxic effects of cisplatin and 5FU in mainly hepatoma cell model, Hep3B and other cell lines namely human colorectal adenocarcinoma cell line HT29 and human prostate cancer cell line PC3.…”
Section: Discussionmentioning
confidence: 99%